Effect of intercropping on high yielding fodder production in bathan areas of Sirajgonj district (Bangladesh Journal of Animal Science, 2015)
The experiment was conducted at Bajar Para bathan of Shajadpur upazila under Sirajgonj district to study the effects of intercropping on high yielding fodder production in Bathan areas of Sirajgonj district. In this experiment, fodders were cultivated in 27 experimental plots of each size (15×15m) were arranged in 9 treatments as Khesari (Sole), Napier dwarf early, Napier dwarf late, Splendida, Jumboo, Khesari+Napier dwarf early, Khesari+Napier dwarf late, Khesari+Splendida and Khesari+Jumboo. The biomass yield of Napier dwarf early, Napier dwarf late, Splendida and Jumboo as sole crop were 100.32, 90.26, 72.31 and 48.33 ton/ha., respectively. The yield of Khesari was 58.76 ton/ha. as sole crop and differs significantly (p